Cyclometalated platinum(II) complexes bearing eugenol as effective catalyst for hydrosilylation of phenylacetylene by triethoxysilane - Thong, Pham Van; Trang, Dinh Ngoc Doan; Hang, Truong Thuy; Nguyen Thi Thanh Chi, (Vietnam Journal of Science and Technology, 2024)
The catalytic activities of the platinacyclic complexes bearing eugenol (EugH) including [Pt(μ-Cl)(Eug)]2 (1) and [PtCl(Eug)(amine)] (2–4) [amine: pyridine/2, 4-methylpyridine/3, quinoline/4] for hydrosilylation of phenylacetylene by triethoxysilane have been studied for the first time. The results showed that the complexes 1–4 exhibited good catalytic abilities. With loading 0.5 mol% each of the catalysts 1–4 at 70 oC without solvents and any other additives in the air for 2 hours, the triethoxysilane was completely converted to (E)-triethoxy(styryl)silane) (β(E) – the major product) and (triethoxy(1-phenylvinyl)silane) (α – the minor product) with the α/β(E) molar ratio ranging from 1 : 2.6 to 1 : 2.8. At the same reaction conditions with loading 0.1 mol% each of the catalysts 2–4, the conversion of triethoxysilane slightly reduced with an efficiency of 97–99% and the α/β(E) molar ratio of 1 : 2.6 indicating the important role of the Pt-(C=Calkene) in 1–4 for their catalytic activity. Furthermore, the verification of structures of complexes 2–4 by 13C NMR spectroscopy indicated that in chloroform-d1, complex 3 formed two distinct structural forms due to strong intermolecular interactions between the chloroform solvent and the complex, including a Cl3C-H...ClPt(II) hydrogen bond and a Cl2HC-Cl...Pt(II) halogen bond.